Les femmes dans les conflits entre agriculteurs et éleveurs – études de cas du Soudan et du Nigeria - Flintan, Fiona E.; Nassef, Magda; Sulieman, Hussein M.; Momale, Saleh (CGIAR System Organization, 2024)
A presentation on women in farmer-herder conflicts - case studies from Sudan and Nigeria, made at a regional roundtable at the Colloquim on (Agro)Pastoralism, Senegal, 12-14th November, 2024.